DAMPAK LIBERALISASI PERDAGANGAN SEKTOR PERTANIAN TERHADAP MAKRO DAN SEKTORAL EKONOMI INDONESIA: PENDEKATAN MODEL EKONOMI KESEIMBANGAN UMUM - . Kasan (Buletin Ilmiah Litbang Perdagangan, 2011)
Recently, trade liberalization issue particularly in agriculture sector has become the main issue in Doha Development Agenda-wTO. Trade liberalization in agriculture sector affected trade flow of primary agriculture products in global market particularly from developing countries to developed countries. This study analyzes the impact of trade liberalization in agriculture sector on macro and economic sectors of Indonesia, using general equilibrium economic model approach by employing gTAp model. It uses the data from the GTAP Version7. The main results show that trade liberalization in agriculture sector benefited developed countries such as the united states of America, Rusia, and european union. On the other hand, some developing countries such as Pakistan, Bangladesh, and Indonesia were negatively affected. furthermore, trade liberalization in agriculture sector reduced output of agriculture sector in Indonesia. nevertheless, the output of manufacturing sector increased because of reallocation of input factor from agriculture to manufacturing.